2016
DOI: 10.4103/2008-322x.183917
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between histopathologic changes and clinical features in pterygia

Abstract: Purpose:To investigate the correlations between clinical findings and histopathologic changes in eyes with pterygium.Methods:This prospective study included 70 eyes with primary pterygia undergoing surgical excision. Prior to surgery, clinical features of the pterygia including extension over the cornea, redness, fleshiness (based on obscuration of the underlying episcleral vessels), and obliteration of the plica semilunaris were determined. Postoperatively, pterygium specimens were examined by hematoxylin-eos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 12 publications
(15 reference statements)
4
20
0
1
Order By: Relevance
“…Nonetheless, the number of new vessels in human pterygium has been reported as extremely variable [19, 20]. In human pterygium, redness and fleshiness are correlated with the vascular density and stromal fibrosis, while the extent of the pterygium over the cornea has an inverse relation with the stromal elastosis [18]. This is in accordance with our results, in which higher redness and vascularization was observed in right eyes.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, the number of new vessels in human pterygium has been reported as extremely variable [19, 20]. In human pterygium, redness and fleshiness are correlated with the vascular density and stromal fibrosis, while the extent of the pterygium over the cornea has an inverse relation with the stromal elastosis [18]. This is in accordance with our results, in which higher redness and vascularization was observed in right eyes.…”
Section: Discussionsupporting
confidence: 90%
“…However, larger lesions over the cornea may be associated with increased thickness and volume of the pterygium body, resulting in higher grades of redness and fleshiness. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Pterygia were also graded for severity of redness, as follows: grade I: no redness or faint pinkish hue; grade II: scattered areas of moderate redness; and grade III: significant and diffuse redness. [ 8 ] Exclusion criteria were previous medical treatment for pterygium including topical steroids or non-steroidal anti-inflammatory drugs, previous conjunctival surgery, conjunctival cicatricial disease, systemic autoimmune disease, and untreated dry eye disease. All patients were treated using the same surgical technique (excision and graft).…”
Section: Methodsmentioning
confidence: 99%
“…Pterygium is a fibrovascular neoformation composed of epithelium and highly vascular loose subepithelial connective tissue (20). Previous studies have demonstrated that apoptotic and oncogenic proteins, microsatellite instability, inflammatory mediators, extracellular matrix modulators, EMT and other factors are involved in the development of pterygium (4,(9)(10)(11)13).…”
Section: Discussionmentioning
confidence: 99%